The Institutionalization Problem of Competitive Intelligence in Exporting Firms: Descriptive Findings and Strategic Recommendations (Third Sector Social Economic Review, 2025)
The intensification of global competition, the acceleration of technological innovations, the deepening of economic uncertainties, and the rise of geopolitical risks have made information-based and agile decision-making mechanisms more critical than ever for firms operating in international markets. In this context, competitive intelligence (CI) emerges as a strategic tool that enables firms to monitor environmental developments, identify opportunities, anticipate threats, determine strategic direction, and support decision-making processes. In this study, competitive intelligence (CI) is addressed from both conceptual and practical perspectives within the context of exporting firms. The historical development of CI, its core processes, and its position in the literature are examined. The reviewed literature indicates that CI enhances firms' strategic decision-making capabilities and significantly contributes to gaining competitive advantage. However, as in many other countries, CI practices in Türkiye are largely limited to informal structures, and the institutionalization level of CI systems remains insufficient. In line with the purpose of the study, a descriptive research design was adopted. The sample of the research consists of 356 exporting firms operating in the province of Ankara. Descriptive analysis findings reveal that these processes are mostly carried out by marketing departments and that the level of CI implementation is moderate. The study is expected to contribute to both practitioners and policymakers by offering recommendations for the development of ethical and technology-supported CI systems.
Keywords: Competitive Intelligence; Competitive Intelligence Process; Exporting Firms; Institutionalization of Intelligence; international trade